Primary immunodeficiency: common variable immunodeficiency - Oksana Ussenova; Dinara Gabdullina; Marina Morenko; Yelena Kovzel (National Scientific Medical Center, 2016)
By definition, primary immunodeficiencies are genetically determined diseases, which are fundamental molecular or organic defects associated with impaired immune responses, in this case there is the clinic of infectious and autoimmune diseases, with an increased risk of developing malignancies. Primary immunodeficiency diseases more frequent than previously thought. The lack of clear algorithms and the use of outdated technologies considerably delay diagnosis process, which leads to delays expensive no specific treatment instead of Immunotropic effective therapy. The first episodes of primary immunodeficiencies (PID) are manifested at an early age, but also the primary PID can also occur in adults, the first episode of the disease observed in the 20-30 years of age.